2014
DOI: 10.7763/ijapm.2014.v4.271
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Optical Studies of Rare Earth Doped Tungston–Tellurite Glasses

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…5,6 Thermal properties of tellurite glasses from the TeO 2 -WO 3 -La 2 O 3 and TeO 2 -WO 3 -PbO have been extensively studied by D. Sushama and P. Predeep. 7 They have found that tellurite glasses containing La 2 O 3 are thermally more stable than the tellurite glasses containing PbO. The positive inuence of lanthanum oxide addition on the thermal stability of glasses of the TeO 2 -WO 3 -PbO-La 2 O 3 system has been conrmed by earlier papers.…”
Section: Introductionmentioning
confidence: 83%
“…5,6 Thermal properties of tellurite glasses from the TeO 2 -WO 3 -La 2 O 3 and TeO 2 -WO 3 -PbO have been extensively studied by D. Sushama and P. Predeep. 7 They have found that tellurite glasses containing La 2 O 3 are thermally more stable than the tellurite glasses containing PbO. The positive inuence of lanthanum oxide addition on the thermal stability of glasses of the TeO 2 -WO 3 -PbO-La 2 O 3 system has been conrmed by earlier papers.…”
Section: Introductionmentioning
confidence: 83%
“…Such reduction in defects is strongly related to the decreasing number of the NBO, by forming more bridging oxygen (BO) network bonds. It is suggested, further addition of Er 2 O 3, its role as intermediate oxides glass modifier possibly has partly become as lattice former especially at higher concentration [10]. This has created more denser and cross-linking tightly packed glass network structure.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, TeO2 based glasses have gained more focusing from many researchers and investigators due to their unique features such as high linear and nonlinear refractive indices and good shield for radiations [11,15,[19][20][21][22]. Therefore, glasses with TeO2 as a former have many beneficial uses in the solid-state lasers applications, memory switching instruments, and solar cells [23][24][25].…”
Section: Introductionmentioning
confidence: 99%